2018
DOI: 10.1016/j.kjms.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cutaneous T‐cell attracting chemokine elevation and adipose‐derived stromal cell migration in a high‐glucose environment cause poor diabetic wound healing

Abstract: Diabetic wound care is a major health care concern. The major cause of non‐healing of wounds in patients with diabetes mellitus (DM) patients mainly involves poor glycemic control, which hinders the migration of progenitor cells including mesenchymal stem cells to the wound site. In this study, we introduced adipose‐derived stromal cells (ADSCs) into wound sites and demonstrated that the local transplantation of ADSCs accelerated DM‐related wound healing. Furthermore, the migration ability of ADSCs, which dimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…The involvement of lymphocytes takes place in a second stage beyond the first 72 h, having a role in modulating the healing processes through the synthesis of the extracellular matrix and the remodeling collagen. There are studies in which the inhibition of T lymphocytes has resulted in decreased healing tissue resistance and poor collagen synthesis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of lymphocytes takes place in a second stage beyond the first 72 h, having a role in modulating the healing processes through the synthesis of the extracellular matrix and the remodeling collagen. There are studies in which the inhibition of T lymphocytes has resulted in decreased healing tissue resistance and poor collagen synthesis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst MSCs, highly abundant and easily obtainable adipose-derived stem cells (ASCs), have been well recognized to be another promising candidate applying in diabetic wound healing [ 107 ]. ASCs share a high similarity of phenotypic and functional characteristics with bone marrow-derived MSCs as ASCs not only present with the capacity to differentiate into diverse cell lineages, such as adipogenesis, chondrogenesis, osteogenesis, and myogenesis [ 108 ], but also promote cell growth and accelerate wound healing by secreting a multitude of growth factors including VEGF, FGF, and HGF [ 109 ].…”
Section: Stem Cell Therapy In Diabetic Wound Healingmentioning
confidence: 99%
“…We have discovered that local administration of ASCs into the wound margin triggered angiogenesis and increased tissue regeneration, which further promoted diabetic wound healing through paracrine and autocrine mechanisms including an increase in von Willebrand factor and VEGF in streptozotocin (STZ)-induced diabetic rodent model [ 110 ]. We have also reported that the exogenous replenishment of the cutaneous CTACK/CCL27 at least partially restored the migration ability of ASCs, which was diminished in a high-glucose condition, and might eventually improve diabetic wound healing [ 107 ]. These studies strongly suggest that delayed wound healing in patients suffering from diabetes may be attributed to suppressed expressions of growth factors and regulatory cytokines such as CTACK/CCL27, which further lead to a deficient stem cell migration to the wound sites, thus implicating that the exogenous administration of ASCs contribute to diabetic wound healing.…”
Section: Stem Cell Therapy In Diabetic Wound Healingmentioning
confidence: 99%
“…Экспрессия CCL27 нарушена в тканях при диабете. Отсутствие CCL27 снижает привлечение T-клеток к поврежденным тканям, что является одной из причин плохого заживления тканей при диабете [112].…”
Section: индикаторы воспалительного старенияunclassified